Analysis of Symbolic Interactionism on Mbayar Tukon Marriage Tradition in Sumurarum Village, Grabag District, Magelang Regency - Ibnu Azkaa Athoillah (QURU’: Journal of Family Law and Culture, 2023)
Mbayar Tukon tradition is a cultural practice of marriage that is still preserved in Sumurarum Village, Grabag District, Magelang Regency. In this study, Herbert Blumer's Symbolic Interactionism theory is applied to understand the meaning, interpretation, and social interaction associated with this tradition. Through a qualitative approach using in-depth interviews and participatory observation, data was collected from tukon givers and receivers as well as local community leaders. The results of the analysis show that the Mbayar Tukon tradition is not only a material act, but also has a deep symbolic meaning in the context of marriage and local culture. The interaction between individuals in this tradition strengthens their identity in society, as well as deepening social relations between families and communities. This tradition also plays a role in shaping social reality and maintaining cultural heritage in Sumurarum Village. Thus, the application of Herbert Blumer's Symbolic Interactionism theory provides a deeper understanding of the role of the Mbayar Tukon tradition in shaping identity, social relations, and social reality in the context of the local community of Sumurarum Village, Grabag District, Magelang Regency.